Counseling antifumo in un gruppo di lavoratori ex esposti ad asbesto / Anti-smoking counseling in a group of workers with past exposure to asbestos - D' Agostin, Flavia; Negro, C.; Barbati, Giulia; De Zotti, Renata (La Medicina del Lavoro, 2012)
Summary«Anti-smoking counseling in a group of workers with past exposure to asbestos». Background: Anti-smoking counseling is often part of healthcare protocols for workers with past asbestos exposure; nevertheless, data is lacking about the results. Objectives: To evaluate smoking habits and the effects of anti-smoking counseling in a group of workers with past asbestos exposure. Methods: Smoking was assessed in 671 subjects who voluntarily attended a health surveillance protocol. Fagerstrom’s and Richmond’s tests were used in order to estimate smokers’ addiction and their potential will to quit. Besides anti-smoking counseling, smokers were also offered a formal cessation programme. Results: The mean age of the 671 subjects was 66 (DS= 7,9) years. The population consisted of 87 (13%) current smokers, 372 (55%) ex-smokers and 212 (32%) non smokers. According to Fagerstrom’s test results, only 10% of the smokers presented a strong/very strong addiction, while Richmond’s test results showed that 50% of the smokers had a strong/very strong will to quit. Only one smoker decided to join a cessation programme. Conclusions: The results of the study could present a bias, because volunteer-based protocols may promote the participation of self-motivated and health-sensitive subjects. This could be one of the reasons for the low prevalence of current smokers and high prevalence of ex-smokers. Anti-smoking counseling did not produce satisfactory effects because smokers were resistant to quitting smoking. Identification of anti-smoking counseling weak points may improve efficacy in health prevention controls made on subjects with past asbestos exposure. RiassuntoIntroduzione: Programmi che favoriscono l’astensione dal fumo di sigaretta sono frequentemente inseriti nei controlli sanitari per i lavoratori ex esposti ad asbesto, ma i dati sulla loro efficacia sono carenti. Obiettivi: Valutare l’abitudine al fumo di sigaretta e i risultati del counseling antifumo in un gruppo di lavoratori ex esposti ad asbesto. Metodi: È stata esaminata l’abitudine al fumo in 671 soggetti che avevano aderito su base volontaria ad un protocollo sanitario. Nei fumatori, i test di Fagerstrom e di Richmond sono stati utilizzati per valutare la dipendenza e la motivazione alla cessazione dal fumo. Oltre al counseling antifumo, è stato predisposto un percorso privilegiato per la disassuefazione dal fumo. Risultati: L’età media è risultata di 66 (DS=7,9) anni. I fumatori correnti erano 87 (13%), gli ex fumatori 372 (55%) e i non fumatori 212 (32%). In base al test di Fagerstrom solo il 10% dei fumatori ha dimostrato una dipendenza dal fumo “alta/molto alta”, mentre il test di Richmond  ha  evidenziato una motivazione a smettere di fumare “alta/molto alta” nel 50% dei fumatori. Solo un fumatore ha iniziato un percorso di disassuefazione. Conclusioni: L’adesione volontaria ai controlli può aver favorito la partecipazione di soggetti motivati ed attenti agli aspetti sanitari. È possibile che questo sia uno dei motivi per cui i fumatori risultavano la minoranza, peraltro riluttanti ad intraprendere un percorso di disassuefazione. I risultati del counseling antifumo non sono stati soddisfacenti, ma l’esperienza è importante per  identificare i punti deboli e migliorare l’efficacia di interventi antifumo tra gli ex esposti ad asbesto.